Cancer-Targeted Azo Dye for Two-Photon Photodynamic Therapy in Human Colon Tissue - Lee, Dong Joon; Juvekar, Vinayak; Lee, Hyo Won; Kim, Eun Seo; Noh, Choong Kyun; Shin, Sung Jae; Kim, Hwan Myung (Analytical Chemistry, 2021)
Inappropriate cancer management can be prevented by simultaneous cancer diagnosis, treatment, and real-time assessment of therapeutic processes. Here, we describe the design of a two-photon (TP) photosensitizer (PS), ACC-B, for high temporal and spatioselective near-infrared cancer therapy. ACC-B consisting of a biotin unit significantly enhanced the cancer sensitivity of the PS. Upon TP irradiation, ACC-B generated reactive oxygen species (ROS) through the type I photodynamic therapy (PDT) process and triggered highly selective cancer ablation. In addition, fluorescence microscopy images revealed that ACC-B-loaded live human colon tissues showed a marked difference in ACC-B uptake between normal and cancer tissues, and this property was used for real-time imaging. Upon 770 nm TP treatment, ACC-B generated ROS efficiently in live colon cancer tissues with high spatial selectivity. During PDT, ACC-B can provide in situ spatioselective visualization of cellular behavior and molecular information for therapeutic assessment in specific regions.
Keywords: Azo-dyes; Cancer diagnosis; Cancer management; Cancer tissues; Colon tissues; Human colon; Photosensitiser; Reactive oxygen species; Two photon; Two-photon photodynamic therapies